2001
DOI: 10.1046/j.0305-1846.2000.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of swainsonine, captopril, tangeretin and nobiletin on the biological behaviour of brain tumour cells in vitro

Abstract: Although intrinsic tumours of the brain seldom metastasize to distant sites, their diffuse, infiltrative-invasive growth within the brain generally precludes successful surgical and adjuvant therapy. Hence, attention has now focused on novel therapeutic approaches to combat brain tumours that include the use of anti-invasive and anti-proliferative agents. The effect of four anti-invasive agents, swainsonine (a locoweed alkaloid), captopril (an anti-hypertensive drug), tangeretin and nobiletin (both citrus flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…In human MCF-7/6 breast carcinoma cells, tangeretin treatment effectively inhibited the metastasis by down-regulating MMP-2 and MMP-9 in breast cancer [94]. In melanoma, the invasion of B16F10 cells was inhibited by the treatment of tangeretin [111]. Moreover, wound healing assay showed that tangeretin exerted inhibitory effects on SKOV3 cell migration.…”
Section: Anti-metastasismentioning
confidence: 83%
“…In human MCF-7/6 breast carcinoma cells, tangeretin treatment effectively inhibited the metastasis by down-regulating MMP-2 and MMP-9 in breast cancer [94]. In melanoma, the invasion of B16F10 cells was inhibited by the treatment of tangeretin [111]. Moreover, wound healing assay showed that tangeretin exerted inhibitory effects on SKOV3 cell migration.…”
Section: Anti-metastasismentioning
confidence: 83%
“…36) Of importance, other groups have found that NOB suppressed MMP-9 expression in interleukin-1-treated rabbit synovial fibroblasts, 20) as well as in phorbol ester-stimulated HT-1080 21) and in some brain tumor cell lines that showed a constitutive expression of MMP-9. 22) In addition, inhibition of MMP-9 production by NOB in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, thecatenin/TCF complex is known to cooperate with AP-1 for maximum expression. 14) While there are a large number of reports regarding MMP-9 suppressants, including catechins, 15) curcumin, 16) 1,25-dihydroxyvitamin D 3 , 17) peroxisome proliferator-activated receptor (PPAR) activators, 18) inhibitors of cyclooxygenase (COX) and phospholipase A 2 , 19) and nobiletin (NOB), [20][21][22][23] those for MMP-7 are limited (e.g., retinoic acid, 24) butyrate, 25) and PPAR agonist troglitazone 26) ). In the present study, we investigated the expression of MMPs in human colorectal cancer cell lines and found a high level of MMP-7 mRNA in HT-29 cells.…”
Section: )mentioning
confidence: 99%
“…The upregulation in glioma cells of specific members of the MMP family, such as MMP2 and MMP9 (reviewed in [12,21,22]), and the decrease of glioma invasion through inhibition of these enzymes [23][24][25][26][27] have encouraged the design of adjuvant therapies based on targeting MMP activity. However, clinical trials of MMP inhibitors have proven disappointing due to lack of effect or damaging side-effects [28][29][30].…”
Section: Introductionmentioning
confidence: 99%